APLIKASI ALGORITMA BRANCH AND BOUND UNTUK MENYELESAIKAN INTEGER PROGRAMMING - Enty Nur Hayati (Jurnal Ilmiah Dinamika Teknik, 2010)
Integer Programming represents one of the modeling for seeking an optimum solution from a problem. A lot of case around us needing programming integer implementation so that got a solution most optimal which is on finally add advantage. There is many way of to finish programming integer, for example by standard linear program that is by using graph. Way of other is with algorithm application of Branch Bound and. This Handing out try to explain how a programming integer finished with algorithm application of Branch Bound and. Keywords: Branch and Bound, Integer Programming, BFS, DFS